Efficacy of topotecan in pretreated metastatic poorly differentiated extrapulmonary neuroendocrine carcinoma - Apostolidis, Leonidas; Bergmann, Frank; Jäger, Dirk; Winkler, Eva C. (Cancer medicine, 2016)
Therapeutic options for metastatic poorly differentiated neuroendocrine carcinoma (NEC) after prior platinum‐based chemotherapy are limited. Topotecan is an approved second‐line chemotherapy for small cell lung cancer (SCLC). NEC is often considered to show a biological behavior similar to SCLC. The aim of this study was to analyze the efficacy of topotecan in pretreated metastatic NEC patients. We performed a retrospective analysis of all patients treated with topotecan for metastatic NEC who presented at our center between January 2005 and December 2014 (n = 30). All 30 patients had received at least a platinum and etoposide containing regimen as prior chemotherapy. Median proliferation rate (Ki67) was 80%. As best response to topotecan five patients showed a stable disease, two patients a partial remission, resulting in a disease control rate of 23%. Of the remaining 23 patients, 14 (47%) showed a progressive disease, nine (30%) died before radiologic response could be evaluated. Median progression‐free (PFS) and overall survival (OS) after start of topotecan was 2.1 and 4.1 months, respectively. In the subgroup analysis, patients with unknown primary (vs. those with a known primary) showed a significantly prolonged PFS of 3.5 months (vs. 1.9, P = 0.0107) and OS of 6.7 months (vs. 2.6 months, P = 0.0168). Grade 3/4 hematotoxicity was observed in 60% of patients. Topotecan shows only moderate antitumor activity in metastatic NEC. Disease control rate is lower than reported for SCLC. However, antitumor activity of topotecan seems higher in patients with unknown primary.